1998
DOI: 10.1162/106454698568576
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of Research on Self-Replication: An Overview

Abstract: The study of self-replicating structures or machines has been taking place now for almost half a century. My goal in this article is to present an overview of research carried out in the domain of self-replication over the past 50 years, starting from von Neumann's work in the late 1940s and continuing to the most recent research efforts. I shall concentrate on computational models, that is, ones that have been studied from a computer science point of view, be it theoretical or experimental. The systems are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(91 citation statements)
references
References 39 publications
1
90
0
Order By: Relevance
“…In the context of abstract tile pattern self-replication model, it is tempting to draw a comparison between the CA-based self-replication loops [15]. In particular, the parameters, such as loop sizes and replication periods of different CA based self-replicating loops resemble with the terms, pattern size and replication time of the abstract tile pattern self-replication model.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In the context of abstract tile pattern self-replication model, it is tempting to draw a comparison between the CA-based self-replication loops [15]. In particular, the parameters, such as loop sizes and replication periods of different CA based self-replicating loops resemble with the terms, pattern size and replication time of the abstract tile pattern self-replication model.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Von Neumann found that the large state space was necessary for self-replication. Over the years, his schemes have been simplified and extended (Chou and Reggia, 1998;Nobili et al, 1994;Penrose, 1958Penrose, , 1959Sipper, 1998), though they have never been realized in practice. The rules of cellular automata are arbitrary and disconnected from fundamental physical constraints that apply to actual objects like colloids, which are subject to thermal fluctuations and whose interactions are limited by their surface chemistry.…”
Section: List Of Figures 28mentioning
confidence: 99%
“…Applications of self-replicating machines have been proposed ranging from space exploration [3] [4], construction of solar power arrays [5], desktop rapid manufacturing [6] [7] [8], and nanotechnology. Reviews of much of this research are presented in [9] [10].…”
Section: Introductionmentioning
confidence: 99%